Two year comparative outcomes of drug coated balloons in long versus short femoropopliteal lesions - Yuru Wang; Kang Li; Jiang Shao; Zhichao Lai; Yiyun Xie; Deqiang Kong; Bao Liu (Scientific Reports)
Abstract While the efficacy and safety of drug-coated balloons (DCBs) for treating short femoropopliteal lesions are well-established, evidence on long-term outcomes for long lesions remains limited. This study aims to compare the 2-year clinical outcomes of DCB angioplasty between long and short femoropopliteal lesions and identify risk factors for patency loss. This real-world and single-center cohort study included 234 patients with de novo stenosis or restenosis or occlusion of the femoropopliteal arteries (115 long lesions > 15 cm, 141 short lesions ≤ 15 cm) who underwent successful DCB treatment from January 2019 to December 2021 at Peking Union Medical College Hospital. The primary safety endpoint was defined as freedom from major adverse events (death, target limb amputation or thrombosis). The primary effectiveness endpoint was defined as 2-year primary patency, defined as freedom from both clinically driven target lesion revascularization (CD-TLR) and restenosis. Primary patency was significantly lower in long lesions (48.3% vs. 62.5%, p = 0.005), while freedom from CD-TLR rate showed no difference (83.6% vs. 87.4%, p = 0.25). Long lesions exhibited higher rates of occlusions (p < 0.001), in-stent restenosis (p = 0.025), and advanced ischemia (Rutherford Clinical Category (RCC) 4–6, p = 0.038). Multivariate analysis identified lesion length > 15 cm (p = 0.017) and RCC 4–6 (p = 0.026) as independent predictors of patency loss. Within the long lesion subgroup, only RCC 4–6 maintained prognostic significance (p = 0.027), and no significant predictors emerged in the short lesion group. Major adverse events occurred in 12.4% of patients, predominantly in long lesions with severe comorbidities. While DCB angioplasty achieved acceptable 2-year safety outcomes, long femoropopliteal lesions (> 15 cm) demonstrated significantly inferior primary patency compared to short lesions (48.3% vs. 62.5%, p = 0.005). Advanced ischemia (RCC 4–6) is a risk factor for patency loss.